Rancang Bangun Sistem Deteksi Gestur Tangan untuk Pengendalian Slide Presentasi menggunakan Algoritme You Only Look Once Versi 3 - Muhammad Rafi Zaman; Fitri Utaminingrum (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Presentations have become part of the delivery of information that is very often used. However, in controlling the presentation, they still use a third device to control the presentation, such as the keyboard, mouse, and pointer. This is considered to be less effective like a keyboard and mouse because the presenter has to make a presentation by sitting in front of the screen so that it interferes with the presenter's focus and does not look natural like a pointer. Another solution that can be used as a presentation controller is human hand gestures. This study aims to create a hand gesture detection and recognition system to control presentation applications. This system will issue an output in the form of a simulated keyboard and mouse pressure. To be able to recognize hand gestures, the system uses one of the deep learning methods, namely You Only Look Once version 3 with an NVIDIA Jetson Nano device as a test. This system is designed to detect hand gestures within a distance of 1 to 2.5 meters. The training data used in this system are 7080 images of training data with 8 classes of hand gestures and the training data is taken with a predetermined distance. The results of system testing based on distance produce an average accuracy value of 91.18%. And the average computation time is 0.5988 seconds.